An unusual tumor of the spermatic cord: myositis ossificans - (:unkn) unknown (My University, 2003)
OBJECTIVES: Tumors of the spermatic cord and epididymis are rare, and their exact incidence is difficult to determine. Ninety percent of extra testicular tumors within the scrotum are found in the spermatic cord, where 30% is malignant (1). METHODS: In this case report we present an unusual spermatic cord tumor, i.e. myositis ossificans (MO). To the best of our knowledge, MO of the spermatic cord has not been reported before in the literature. CONCLUSIONS: MO should be considered in the differential diagnosis of the spermatic cord tumors.
Keywords: Humans; Middle Aged; Male; Spermatic Cord; Genital Diseases, Male; Myositis Ossificans